Culture Jamming : Activism and the Art of Cultural Resistance - Fink, Moritz; DeLaure, Marilyn (Book collections on Project MUSE., 2017)
Coined in the 1980s, culture jamming refers to an array of tactics deployed by activists to critique, subvert, and otherwise jam the workings of consumer culture. Ranging from media hoaxes and advertising parodies to flash mobs and street art, these actions seek to interrupt the flow of dominant, capitalistic messages that permeate our daily lives. Employed by Occupy Wall Street protesters and the Russian feminist punk band Pussy Riot alike, culture jamming scrambles the signal, injects the unexpected, and spurs audiences to think critically and challenge the status quo. The essays, interviews, and creative work assembled in this unique volume explore the shifting contours of culture jamming by plumbing its history, mapping its transformations, testing its force, and assessing its efficacy. Revealing how culture jamming is at once playful and politically transgressive, this accessible collection explores the degree to which culture jamming has fulfilled its revolutionary aims. Featuring original essays from prominent media scholars discussing Banksy and Shepard Fairey, foundational texts such as Mark Dery s culture jamming manifesto, and artwork by and interviews with noteworthy culture jammers including the Guerrilla Girls, The Yes Men, and Reverend Billy, "Culture Jamming" makes a crucial contribution to our understanding of creative resistance and participatory culture.